The Alignment of Strike Regulations in Article 256 of the Criminal Code with Human Rights Principles - Ameilia, Viera; Rizanizarli; A. Gani, Iskandar (International Journal of Law, Crime and Justice, 2026)
The reform of criminal law through Law Number 1 of 2023 concerning the Criminal Code introduces provisions on demonstrations in Article 256, which impose criminal sanctions on organizers who fail to notify authorities when activities potentially disrupt public interest or public order. This provision has generated debate from a human rights perspective due to the ambiguity of the phrase “disruption of public interest” and the broad discretion granted to law enforcement officials. In practice, such discretion is reflected in the prohibition of demonstrations, refusal to issue Acknowledgment of Receipt of Notification Letters (STTP), and even the dissolution of activities, despite the legal framework requiring only notification rather than permission. This study aims to analyze the conformity of Article 256 of the Criminal Code with human rights principles. The research employs a normative juridical method using statutory and conceptual approaches. Data were collected through library research and document studies of primary, secondary, and tertiary legal materials, then analyzed qualitatively using descriptive-analytical and prescriptive methods through legal interpretation and argumentation. The findings indicate that, normatively, Article 256 is generally consistent with human rights principles because it seeks to balance freedom of assembly with the protection of public interests and reflects the principles of universality, inalienability, and state obligation. However, challenges remain in its implementation, particularly regarding vague legal norms, broad official discretion, and the risk of disproportionate restrictions. These issues may affect the principles of non-discrimination and the protection of freedom of expression and assembly. Therefore, the implementation of Article 256 requires greater consistency, proportionality, and clearer limitations on official discretion to ensure compliance with human rights standards.